1998
DOI: 10.1016/s0167-6636(97)00062-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational study of fracturing in an anisotropic brittle solid

Abstract: For isotropic materials, stress-and energy-based fracture criteria lead to fairly similar results. Theoretical studies show that the crack-path predictions made by these criteria are not identical in the presence of strong material anisotropy. Therefore, experiments are performed to ascertain which criterion may apply to anisotropic materials. Notched specimens made from sapphire, a microscopically homogeneous and brittle solid, are used for the experiments. An attempt is made to locate the notch on different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Moreover, single crystal materials have a discrete number of cleavage planes and do not always fracture in the direction of the highest tensile stress, but rather in the direction where a high tensile stress acts on a weak cleavage plane. This was supported experimentally [26] and the results on notched A-plane sapphire specimens showed that the energy criterion fails to predict the fracture path of most of the specimens. A dimensionless parameter A was introduced to measure the onset of crack initiation.…”
Section: Fracture In An R-plane Wafersupporting
confidence: 52%
See 2 more Smart Citations
“…Moreover, single crystal materials have a discrete number of cleavage planes and do not always fracture in the direction of the highest tensile stress, but rather in the direction where a high tensile stress acts on a weak cleavage plane. This was supported experimentally [26] and the results on notched A-plane sapphire specimens showed that the energy criterion fails to predict the fracture path of most of the specimens. A dimensionless parameter A was introduced to measure the onset of crack initiation.…”
Section: Fracture In An R-plane Wafersupporting
confidence: 52%
“…Reports on γ λ of different cleavage planes in single crystal sapphire [26] show that the strongest plane is the basal c-plane (0 0 0 1) having γ λ > 40 J/m 2 , and the weakest family of planes is {1 0 1 2} having γ λ = 6 J/m 2 . The other families of cleavage planes are stronger: {11 2 6} with γ λ = 24.2 J/m 2 and {1 01 0} with γ λ = 7.3 J/m 2 .…”
Section: Fracture In An R-plane Wafermentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest surface energies are found for the f10 10g and f 1012g planes. 24 The orientation of the lateral surface in our sample was determined to be ð10 10Þ by means of XRD measurements. Figure 3 shows the polarized Raman spectra obtained from the ð10 10Þ lateral face.…”
Section: Resultsmentioning
confidence: 99%
“…While most theoretical and computational studies have focused on elastic anisotropy [1][2][3], the anisotropy of the fracture toughness influences more strongly the crack propagation of a wide variety of materials including single crystals [4][5][6], extruded polymers [7], geological materials [8,9], including sedimentary [10] and granitic rocks [11], or apple flesh [12]. The issue of brittle crack propagation in materials with anisotropic surface energy deeply interrogates our understanding of fracture and is receiving increasing attention from a variety of points of view, such as molecular dynamics [13], continuum mechanics [14,15], phase-field modeling [16,17], and experiments [7,18]. Here, by exploiting the analogy with crystal growth, we develop and implement numerically a phase-field model for brittle fracture of materials with strongly anisotropic surface energy and interpret our numerical results in the light of recent theories and experiments.…”
Section: Introductionmentioning
confidence: 99%